A Study Of Strategies Adopted To Combat Counterfeit Culture By Luxury Brands – A Comparative Study Between Gucci And Louis Vuitton - Budiyono, Ibadurohmah; Novitasari, Sela (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
Counterfeiting of well-known luxury brands with a great brand identity and high exposure is a global industry that is rapidly expanding. Perhaps counterfeiting has become the world's fastest growing and most viable business, and there are no signs that the industry is slowing down, particularly when more luxury brands have clearly externalized signs of recognition. It is difficult to estimate the size of the counterfeit merchandise industry since it operates on a ‘gray market.’ According to one estimate, counterfeiting accounts for more than 6% of global trade, or $450 billion a year, and fake products worth $100 million are intercepted per year entering the United Arab Emirates (Betts, 2019). With the introduction of the Internet as a business development channel, the issue of counterfeit products has become even more critical for luxury brands. The counterfeit merchants are offering a serious threat to the luxury houses, with professional-looking websites, low prices, quicker delivery times, and a wider variety of delivery options. The luxury brands are losing a lot of money and are retaliating by spreading the word that purchasing counterfeit goods helps promote terrorism and other not just illegal but also morally reprehensible practices. Suppliers of counterfeit goods, including luxury conglomerates, have recognized the internet's penetration force.